Exploring Strategic Financial Management Techniques in Entrepreneurship: A Detailed Literature Review on Practices That Drive Business Sustainability and Growth - Lumanauw, Bode; Lolowang, Isye Ruth A. (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study examines the strategic financial management techniques that drive business sustainability and growth in entrepreneurship. In the dynamic landscape of modern business, strategic financial management has emerged as a pivotal factor influencing the sustainability and growth of entrepreneurial ventures. This research employs a comprehensive literature review to explore various practices and techniques aimed at optimizing financial resources, ensuring efficient operations, and achieving long-term business objectives. These techniques include budgeting, financial forecasting, investment analysis, capital structure optimization, and risk management. The study identifies financial management practices that have been empirically shown to support business sustainability and growth, providing valuable insights for entrepreneurs and policymakers.